Consumer acceptance of a revolutionary technology-driven product: The role of adoption in the industrial design development. (September 2015) - Park, Jungkun; Gunn, Frances; Lee, YoungHee; Shim, Scott
Abstract: Understanding how consumers adopt a state of the art product is important for the development and marketing of innovative products. The purpose of this study is to examine factors that affect consumer intentions to use a revolutionary technology-driven product (RTP). The research integrates two innovation adoption models, the Unified Technology Acceptance and Utilization Theory (UTAUT) and the Task-Technology Fit (TTF) model with two antecedents of consumer characteristics: consumer innovativeness and perceived value of a new product. The study examines consumer responses to an unfamiliar product, the TEASER which is a conceptual digital cookbook that offers taste sampling, thereby providing an online food-tasting experience. Consumers who are prone to innovativeness and who perceive value in a RTP's aesthetics are able to discern the conditions that support their intent to use such a product. The resulting model expands the UTAUT and TTF theories by showing that UTAUT variables mediate between the variables of TTF and adoption intentions. These results support the need for nonlinear industrial development processes involving consumers. Highlights: This study examines factors that affect consumer intentions to use a revolutionary technology-driven product (RTP). The research integrates two innovation adoption models, the Unified Technology Acceptance and Utilization Theory (UTAUT) and the Task-Technology Fit (TTF) model. Consumers who are prone to innovative and perceive value in a RTP's aesthetics are able to discern the conditions that support their intent to use such a product. These results support the need for nonlinear industrial development processes involving consumers.